The forgotten ways : reactivating apostolic movements - Hirsch, Alan, 1959 October 24- (Grand Rapids, Michigan : Brazos Press, a division of Baker Publishing Group, 2016)
Alan Hirsch's paradigm-shifting classic remains the definitive statement of the church as dynamic missional movement. The bestselling first edition ignited a conversation about how to harness the power of movements for the future growth of the church. In this major update, Hirsch shares significant insights gained along the way, provides fresh new examples of growing churches, and reflects on the last ten years of the missional movement. The new edition has been thoroughly updated and revised throughout and includes charts, diagrams, an expanded glossary of terms, new appendices, an index, a new foreword by Ed Stetzer, and a new afterword by Jeff Vanderstelt. Known for his innovative approach to mission, Hirsch is widely acknowledged as a thought leader and mission strategist for churches across the Western world. He considers The Forgotten Ways the guiding work to all of his other writings. The book explores the factors that come together to generate high-impact, exponentially explosive, spiritually vibrant Jesus movements in any time and context. This extensive update to Hirsch's influential work offers a system of six vital keys to movements that will continue shape the future of the missional movement for years to come. (Publisher).
Section 1. The making of a missionary. A view from the edge: confessions of a frustrated missionary -- A view from above: denominational and translocal perspectives -- Section 2. A journey to the heart of apostolic genius. Preparing for the journey -- The heart of it all: Jesus is Lord -- Disciple making -- Missional-incarnational impulses -- Liminality and communitas -- APEST culture -- Organic systems.
Includes bibliographical references and index.
Keywords: Church; Missions; Postmodernism -- Religious aspects -- Christianity